1994
DOI: 10.1111/j.1365-2362.1994.tb02256.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of α‐glucosidase inhibitors on lipids in NIDDM subjects with moderate hyperlipidaemia

Abstract: This paper summarizes literature data concerning the action of acarbose, an α‐glucosidase inhibitor, on the concentrations of plasma lipids. Clinical trials in which acarbose has been used in the treatment of non‐insulin‐dependent diabetics have sometimes shown that it reduces serum triglycerides while it has little or no effect on serum cholesterol levels. The results of a randomized double‐blind placebo‐controlled study lasting 24 weeks are discussed in more detail. Under the controlled conditions, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Hanefeld et al 85 demonstrated, in a randomised, double-blind, placebo-controlled trial, that acarbose (100 mg three times daily) for 24 weeks as a first line therapy in patients with T2DM (n=94) reduced 1 h postprandial triglyceride levels. Another description by Leonhardt et al 86 showed that acarbose reduced total serum cholesterol and total-to-HDL-cholesterol ratio. Also, after a test meal on day 0 and on week 24 of acarbose treatment, there was a significantly lower postprandial rise in serum triglycerides.…”
Section: Surrogate End Pointsmentioning
confidence: 95%
See 1 more Smart Citation
“…Hanefeld et al 85 demonstrated, in a randomised, double-blind, placebo-controlled trial, that acarbose (100 mg three times daily) for 24 weeks as a first line therapy in patients with T2DM (n=94) reduced 1 h postprandial triglyceride levels. Another description by Leonhardt et al 86 showed that acarbose reduced total serum cholesterol and total-to-HDL-cholesterol ratio. Also, after a test meal on day 0 and on week 24 of acarbose treatment, there was a significantly lower postprandial rise in serum triglycerides.…”
Section: Surrogate End Pointsmentioning
confidence: 95%
“…Also, after a test meal on day 0 and on week 24 of acarbose treatment, there was a significantly lower postprandial rise in serum triglycerides. 86 …”
Section: Surrogate End Pointsmentioning
confidence: 99%
“…Previous clinical trials showed acarbose treatment can reduce elevated cholesterol concentrations in non-insulin dependent diabetics and non-diabetic patients1617. However, another clinical trial showed that in patients with non-insulin-dependent diabetes, acarbose reduces serum triglyceride levels without affecting serum cholesterol levels18. The anti-atherosclerotic mechanism of acarbose beyond glucose lowering is not fully understood.…”
mentioning
confidence: 99%
“…With respect to lipids the major effect is on fasting and pp triglycerides with a reduction of about 15% [39,40]. In addition acarbose reduces atherogenicity of low density lipoproteins in people with IGT [41].…”
Section: Effect On Cardiovascular Risk Factorsmentioning
confidence: 96%